**Answer:**

**Step-by-step explanation:**

x^2 - 4 * x + 4 = (x - 2)^2.

so, this is a quadratic equation, meaning two solutions, and we have a factored form of it, meaning you can get the solutions by simply zeroing out the f(x).

so the zeros/solutions are at x = 3 and x = -11, now, bearing in mind the vertex will be half-way between those two, checking the number line, that midpoint will be at x = -4, so the vertex is right there, well, what's f(x) when x = -4?

P = 2(L + W)

P = 86

L = W + 11

86 = 2(W + 11 + W)

86 = 2(2W + 11)

86 = 4W + 22

86 - 22 = 4W

64 = 4W

64/4 = W

16 = W

L = W + 11

L = 16 + 11

L = 27 <====

G(-1) = -1+3

= 2

F(2) = 5(2) - 10

= 0

Just add them all up that’s it and you will get 20